A Duet, with an Occasional Chorus - Doyle, Arthur Conan, 1859-1930 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Duet, with an Occasional Chorus" by Arthur Conan Doyle is a novel written in the late 19th century. The story revolves around the lives of Frank Crosse and Maude Selby as they navigate the complexities of love, marriage, and personal aspirations leading up to their wedding. Through their correspondence, the book captures their deep affection and the mix of excitement and anxiety that accompanies their impending union. The opening of the novel introduces Frank and Maude through a series of letters that highlight their preparations for marriage, including discussions about the wedding date, the choice of attire, and their hopes for the future. As they share their thoughts and feelings about each other, the reader gains insight into their characters: Frank's self-doubt about providing for Maude and Maude's unwavering love and confidence in their partnership. This correspondence sets the stage for the unfolding dynamics of their relationship, infused with moments of humor, tension, and vulnerability. As the narrative progresses, the importance of their emotional connection amidst societal expectations and personal challenges becomes increasingly evident. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Duet,_with_an_Occasional_Chorus
Release date is 2004-03-01
Transcribed from the 1899 Grant Richards edition by David Price
Keywords: Married people -- Fiction